Iraq Crude Oil Exports – January, February, March/ 2024 - SOMO, Oil Marketing Company (Journal of Petroleum Research and Studies, 2025)
Table 1. Iraq Crude Oil Exports – January 2024 Table 2. Iraq Crude Oil Exports – February 2024 Table 3. Iraq Crude Oil Exports – March 2024